St. Lucia : Statistical Appendix. (IMF Staff Country Reports; Country Report, 2008)
The statistical data on GDP, saving and investment, selected data on the banana industry, selected industrial production, consumer price index, monetary survey, summary operations of the Eastern Caribbean central bank, consolidated accounts of the commercial banks, summary balance of payments, value, volume, and unit value of major exports, imports and prices of petroleum products, merchandise trade volumes, direction of trade, selected tourism statistics, structure of public debt and effective exchange rate indices, and related economic indices have been detailed in this paper.